DEVELOPMENT AND CHARACTERIZATION OF CREAM CONTAINING NANOSTRUCTURED LIPID CARRIERS FOR HAIR SPLIT-END REPAIRING - Prasertpol, Tashatai; Tiyaboonchai, Waree (International Journal of Applied Pharmaceutics, 2019)
Objective: This study aimed to develop the nanostructured lipid carriers (NLCs) for repairing the hair split-end and to compare the influence of NLCs charges on hair binding effects. Methods: NLCs was prepared by a high-pressure homogenization technique. The difference solid lipids were selected to obtain the negatively charged NLCs (N-NLCs) and positively charged NLCs (P-NLCs). The physical characterizations of both NLCs were examined. The NLCs cream was prepared by mixing NLCs into a cream base. Then, the hair split-end binding effects of the NLCs cream were assessed. The physical stability of both NLCs were investigated by kept at room temperature for 6 mo. Results: The N-NLCs and P-NLCs were successfully prepared with a zeta potential of -44.4 mV and 32.3 mV, respectively. They were a spherical shape with a similar mean size of 150-160 nm. The hair split-end evaluation showed that both NLCs illustrated similar hair split-end binding time of more than 3 d, suggesting no extra benefit from the positively charged of P-NLCs. On the contrary, the cream base and commercial product showed a short binding time of <8 h. Furthermore, after 6-mo storage, N-NLCs demonstrated good physical stability without particle aggregation, while P-NLCs exhibited a phase separation. Conclusion: The developed NLCs is a novel alternative for the leave-on product, which would be highly benefits for hair split-end repairing.